Penggunaan Aplikasi RuBer PAI Sebagai Media Pengenalan Dakwah di Kelas 5 SD - Azka Tamalia Andyana Tresna; Viena Aunillah Carl Vinson; Ani Nur Aeni (Prodi PGMI STIT Sunan Giri Bima, 2022)
Da'wah is absolute as the duty of a Muslim. The goal is to bring others to better things. To achieve that goal, it is necessary to pay attention to how one communicates da'wah. The science of preaching must begin to be given from an early age. Later, children can become a person who can preach by Islamic sharia. Based on this, the purpose of this study is to introduce da'wah early on, especially in elementary school-aged children. If taught early on, children can make da'wah a good habit when they grow up. Over time, da'wah is considered a difficult thing to do. Therefore, it is very important to instill religious values in children so that later they become a generation that has commendable morals. In introducing da'wah to children, several ways can be done. One of them, using android-based application media. Like our product, namely RuBer PAI application or Ruang Belajar Pendidikan Agama Islam. In this study, the authors used the Design and Development (D&D) method.